(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2017)
The adventitious components of the model urban flora of Berdyansk, Primorsk and Genichesk (Northern Azov) are characterized. 227 adventitious species of 165 genera and 52 families were founded on the territory of the North Azov Sea region. The importance of research of this plants group is emphasized. To develop ways of their populations regulate number and implement measures on external and internal quarantine. The migration ways and direction, degree of naturalization, primary habitats and time when the adventitious species enter are disscused.